“n” is inversely proportional to t+3. If t = 1 when n = 3, find t when n = 4
Here is my work:
n = k/t +3
3 = k/1+3
3(4) = k
12 = k
... find t when n = 4:
y = 12/n
y = 12/4 = 3/1 = 3
y = 3
Thanks
Nicely done for the first half of your solution,
but after you found k = 12 you made a tiny mistake.
In order to find t, we substitute n by applying the given condition that n = 4.
This operation gives
Then we put them in a better order
At last we find t = 0.
So your work is basically okay but incomplete ~